Information professionals meet Arthur Prior. (March 2020) - Engerer, Volkmar Paul; Sabir, Fatima
The paper investigates the supporting role of information professionals in interdisciplinary digital research projects. It identifies three encounter scenarios in which information professionals meet domain researchers (as research librarian, as information specialist, and as iHumanist) and links them to the domain researchers 'modes of orientation'. We examine these theoretical distinctions by discussing three cases from our own practical engagement in the Prior project. Our discussion shows that the scenarios help to understand information professionals' supporting work, explain the conflicts that emerge, and explicate information professionals' shifting conceptions of what they are doing in terms of the shifting encounter scenarios. In short, the paper presents methodological and theoretical insights that can be useful in understanding encounters between information professionals and domain researchers.